An integrated risk assessment of onshore gas transmission pipelines based on defect population. (15th October 2018) - Witek, Maciej; Batura, Anatolii; Orynyak, Igor; Borodii, Mykhailo
Graphical abstract: Highlights: A novel effective method for risk assessment of gas pipelines is proposed. Failure probability computation for an averaged hypothetical defects population. Recommendations for the minimization of inspection detected defects sizing errors. A method for gas leakage rate estimation for a through pipe wall defect is proposed. A original methodology for the social consequences evaluation is developed. Abstract: The aim of this research is to develop an original probabilistic method for an underground onshore gas transmission pipelines maintenance risk estimation. The method considers a population of the anomalies detected by an in-line inspection . In the methodology, features are considered as a family with certain defect depth and shape distribution derived from the repeated in-line diagnostics of a steel pipeline under operation. A growth rate in the radial direction is determined based on a defects size change between two or more inspections. The number of non-detected hypothetical anomalies were taken into account due to probability of detection and sizing uncertainties by means of a non-perfect inspection device. Metal losses of the pipe wall are assessed by a fracture mechanics method based on a limit load theory and considered as a leak or rupture. Gas pressure distribution and temperature along the pipeline are calculated in steady state conditions. Particular attention was paid to the evaluation of the probabilistic pipeline failure consequences to the surrounding area with parameters as population density and road traffic taken into consideration. Although the presented risk estimation is universally applicable, the novel methodology was applied to the high pressure gas transmission pipeline situated in the area similar conditions typical for Europe. The failure probability calculations are carried out for different pipeline modes of the fluid transportation. A significant connection of the risk evaluation with pressure distribution along the pipeline was observed based on the differences in risk distributions between Summer, Autumn and Winter operational modes.